Frost Defrosting Control System for Air-Source Heat Pump Based on Nighttime Adaptive Image Gray-Scale Recognition - Tang, Haifeng (Journal of Research in Science and Engineering, 2026)
This paper introduces an intelligent defrosting control system for air-source heat pumps based on nighttime adaptive image grayscale recognition. The system aims to address the frequent false actions and low energy efficiency of traditional defrosting technologies (such as the temperature-time method) in low-temperature and high-humidity environments. Its core innovation lies in directly capturing images of the heat exchanger fin surface via a low-illumination camera equipped with infrared fill light and identifying the frost layer using image grayscale processing technology.